2019
DOI: 10.1097/md.0000000000017269
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and clinical characteristics of norovirus gastroenteritis with seizures in children in Taiwan, 2006–2015

Abstract: This study examined the characteristics of norovirus (NoV) gastroenteritis associated with convulsions in children and its molecular epidemiology. From July 2006 through December 2015, NoV infection was confirmed by the genome detection using reverse transcriptase polymerase chain reaction. Viral genotyping with strain validation was achieved using sequence analyses with Basic Local Alignment Search Tool genome identification. The patients’ clinical features were assessed retrospectively, focusing on convulsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 27 publications
4
29
1
Order By: Relevance
“…In addition, we recorded that 38 patients had seizures, accounting for 22.6% of the 168 norovirus-infected children in this study. The result was consistent with previous studies (Chen et al, 2009 , 2019 ; Ma et al, 2019 ), which also showed that norovirus infection has a significantly higher incidence of seizures than rotavirus infection. Seizures, in this study, were similar to benign convulsions associated with mild gastroenteritis reported previously by Chen et al ( 2018 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, we recorded that 38 patients had seizures, accounting for 22.6% of the 168 norovirus-infected children in this study. The result was consistent with previous studies (Chen et al, 2009 , 2019 ; Ma et al, 2019 ), which also showed that norovirus infection has a significantly higher incidence of seizures than rotavirus infection. Seizures, in this study, were similar to benign convulsions associated with mild gastroenteritis reported previously by Chen et al ( 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…Seizures, in this study, were similar to benign convulsions associated with mild gastroenteritis reported previously by Chen et al ( 2018 ). The mechanism of norovirus-induced seizures in children is still unclear, and may be associated with the children’s immature immune system (Chen et al, 2019 ). Recently, some studies found that norovirus infection can cause encephalitis/encephalopathy (Chen et al, 2019 ; Sánchez-Fauquier et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we recorded that 38 (22.6%) patients had seizures, which was the main reason why some patients were admitted. Previous studies have also shown that the probability of seizures in norovirus infections is signi cantly higher than that in rotavirus infections [37][38][39]. Seizures, in this study, were similar to benign convulsions associated with mild gastroenteritis reported previously by Boman et al [40].…”
Section: Discussionsupporting
confidence: 88%
“…Seizures, in this study, were similar to benign convulsions associated with mild gastroenteritis reported previously by Boman et al [40]. The mechanism of norovirus-induced seizures in children is still unclear, and may be associated with the children's immature immune system [37]. Recently, some studies found that norovirus infection can cause encephalitis/encephalopathy [37,41].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation